Organoleptic and Antioxidant Activities of Tomato, Pontianak Orange, and Carrot Juice for Cancer Patients - Nur Rahman; Khairuddin Khairuddin; Ajeng Fasha Shaninditha; Ni Putu Ayuningtyas Mirah Pradnya Dewi; Ary Dwi Ayu Faradina (Indonesian Journal of Human Nutrition, 2023)
Cancer has become a leading cause of mortality worldwide, with approximately 8.2 million deaths attributed to the disease in 2012. Antioxidants have demonstrated potential in combating cancer, and natural sources rich in vitamins, such as fruits and vegetables, are believed to be beneficial. This study aims to assess the chemical and organoleptic qualities of fruit and vegetable juice (tomatoes, Pontianak oranges, and carrots) as functional food for cancer patients. The study used an experimental design with a Complete Randomized Design (CRD) approach, with distinct processing techniques for each treatment level, and three replications were conducted. Data collection involved hedonic scale tests by 20 panelists to evaluate organoleptic quality, spectrophotometric tests to measure vitamin C levels, and DPPH tests to assess antioxidant activity. The results show that the processing of fruit and vegetable juice does not significantly influence vitamin C levels, aroma, or texture (p = 0.50). However, it has a significant effect on antioxidant levels, color, and taste of the juice (p=0.007).